ANALISIS FAKTOR PENENTU TINGKAT EFISIENSI BANK KONVENSIONAL DAN BANK SYARIAH DI INDONESIA PERIODE 2013-2017 DENGAN MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - KURNIANTI, FESTINA; MUSDHOLIFAH, (Jurnal Ilmu Manajemen (JIM), 2019)
Abstract The aim of this research was to analyze the determinant factors that affected the level of bank efficiency of the Conventional banks and Islamic banks. The researcher used the DEA method to get a banking efficiency score in the first stage and Tobit method to analyze the determinant factors that assumed affecting the level of bank efficiency in the second stage. The result obtained in the first stage that showed the average of efficiency level of conventional banks during the period of study was 90.5% (2013), 87.3% (2014), 90.8% (2015), 89.0% (2016), and 85.2% (2017), and for Islamic banks was 99.7% (2013), 99.7% (2014), 96.8% (2015), 97.8% (2016), and 97.6% (2017). The result showed that ROA, Bank Size, and GDP had a significant effect, whereas CAR and NPL variables had no significant effect on the bank efficiency level of the Conventional banks. On the other hand, in Islamic banks, the five variables CAR, ROA, NPF, Bank Size and GDP did not have a significant effect on the level of efficiency of Islamic banks. The results of this research can be used as a benchmark for banks in Indonesia to improve the performance of banking efficiency and the society gets the trust to save their funds in Conventional Banks and Islamic Banks. Keywords: bank efficiency; conventional bank; DEA; Islamic bank. Tobit